ANALYSIS OF THE EFFECT OF ADDITION OF INJECTION PLASTIC SEEDS (HDPE), QUARTZ SAND AND ADDITIVE TO CONCRETE MIXTURE - Tjatur Rahmadi Maulana; Fredy Kurniawan (NAROTAMA UNIVERSITY, Indonesia)
Plastic material is one of many materials that are difficult to decompose naturally and require hundreds of years to decompose completely. One way to reduce the volume of plastic waste is to process or recycle it. Plastic injection seeds (HDPE) is one type of processed plastic waste (HDPE). In this study using the concrete laboratory experimental method according to SNI 03-2834-2000. There are 2 stages in this concrete research, stage 1 is concrete with variations of quartz sand (20%, 30%, and 40%) to the weight of sand and the most optimum results are obtained in concrete mix with 40% quartz sand and 3% additive (TH1 / 40-28) which is equal to 613.1 kg / cm2 in the 28 day test, an increase of 42.34% from the compressive strength of normal concrete K300 of 430.73 kg / cm2. For phase 2, concrete with a variation of quartz sand is 40% and the addition of coarse aggregates from plastic seeds (HDPE) (20%, 30% and 40%) from the weight of gravel and find the most optimal results of concrete mix with 40% quartz, plastic 20% , additive 3% (TH2 / 20-28) which is equivalent to 359.5 kg / cm2 in a 28 day test, a decrease of 41.4% from the compressive strength of concrete stage 1 quartz sand 40% (TH1 / 40-28) from 613, 1 kg / cm2.